Phytoconstituents, bioactivity and antioxidant potential of some commercial brinjal (Solanum melongena L.) cultivars of Bangladesh - Ahmed, Fakhruddin Ali; Mubassara, Sanzida; Sultana, Tania (Jahangirnagar University Journal of Biological Sciences, 2017)
Comparative phytochemical composition, antibacterial activity, cytotoxicity and antioxidant potentiality of seven brinjal cultivars Solanum melongena L. were determined. Strong presence of carbohydrates, phenolic glycosides and weak presence of alkaloids, falvonoids, tannins, terpenoids, steroids and saponins were recorded in all the brinjal varieties. Antibacterial assay of brinjal extracts showed varying degree of sensitivity against both gram-positive and gramnegative bacteria. In cytotoxicity assay, the LC50 values ranged between 59.91 to 216.45 mg/ml after 6 hours was an indication of poor cytotoxic potential of brinjal cultivars. The DPPH free radical scavenging activity ranged between 80.79% to 87.64 although the phenolic content was found between 6.082 to 9.292 mg GAE/g among the brinjal cultivars. Jahangirnagar University J. Biol. Sci. 5(2): 41-50, 2016 (December)